Correlation between anti-cyclic citrullinated peptide antibodies and the severity of clinical manifestation, laboratory manifestation, and radiological joint destruction in rheumatoid arthritis patients - Mat Suwito; Kusworini Handono; Bagus Putu Putra Suryana; Handono Kalim; Cesarius Singgih Wahono (Indonesian Rheumatology Association, 2009)
Background. The second generation anti-cyclic citrullinated peptide test (CCP2) displays sensitivity comparable to that of rheumatoid factor (RF) (approximately 80%) but with superior specificity (98%) . Several observations have indicated that early rheumatoid arthritis (RA) patients with positive anti-CCP may develop a more erosive disease than those without anti-CCP.Objective. The purpose of this cross-sectional study was to investigate the correlation between anti-CCP antibodies and clinical and laboratory parameters and radiological joint destruction in RA patients.Methods. We studied 31 patients with RA fulfilling the 1987 revised criteria of American College of Rheumatology in Rheumatology Clinic of Saiful Anwar General Hospital, Malang, Indonesia. Clinical parameters were collected such as age, sex, visual analog scale,disease duration and diseases activity score (DAS28-3(CRP)). Laboratory parameters were WBC, hemoglobin, platelet count, erythrocyte sedimentation rate, and Creactive protein. Analyzed autoantibody profiles were RF and anti-CCP (ELISA methode). Radiological jointdestruction was evaluated from bilateral postero-anterior manus x ray (Sharp score).Results. Anti-CCP antibodies were detected in 48.4% of RA patients with mean antibody concentration was 291.24Â±143.67 (range 16-523.8) units. Anti CCP level was significantly correlated with duration of RA (month) (p=0.04, r=0.371), RF level (p=0.002, r=0.542) andSharp score (p=0.048, r=0.358), but was not significantly correlated with other clinical and laboratory parameters.Conclusion. Anti-CCP level was correlated with duration of disease, RF, and Sharp score.